2012
DOI: 10.2106/jbjs.k.00694
|View full text |Cite
|
Sign up to set email alerts
|

A Biomechanical Assessment of Soft-Tissue Damage in the Cervical Spine Following a Unilateral Facet Injury

Abstract: The results from this work provide further insight into the expected injury and associated instability present in a traumatic unilateral facet injury in the cervical spine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Further refined categorical descriptions of injury and introductions of graphic representations and example cases may result in higher agreement values. Another factor contributing to ambiguity of facet joint injury categories is that some surgeons consider facet joint injuries with the appearance of a unilateral injury on imaging as a bilateral injury by definition [17]. Some authors have advocated the use of magnetic resonance (MR) imaging for classifying facet joint injuries [18], however, a recent systematic review indicated that MR imaging resulted in poor agreement values for detecting discoligamentous injuries of the thoracolumbar spine [19].…”
Section: Discussionmentioning
confidence: 99%
“…Further refined categorical descriptions of injury and introductions of graphic representations and example cases may result in higher agreement values. Another factor contributing to ambiguity of facet joint injury categories is that some surgeons consider facet joint injuries with the appearance of a unilateral injury on imaging as a bilateral injury by definition [17]. Some authors have advocated the use of magnetic resonance (MR) imaging for classifying facet joint injuries [18], however, a recent systematic review indicated that MR imaging resulted in poor agreement values for detecting discoligamentous injuries of the thoracolumbar spine [19].…”
Section: Discussionmentioning
confidence: 99%
“…Trauma to the cervical spine encompasses a wide spectrum of injuries, ranging from displaced and nondisplaced fractures to subluxed, perched, locked, or dislocated facets, and can be unilateral or bilateral in nature (4,54). The facet capsule, ligamentum flavum, and disc are the most frequently cited areas of soft tissue disruption by these injuries (55)(56)(57). Cervical injuries most frequently occur at levels C5-C6 and C6-C7 (2) and are more common among males (52,58), people 15-45 years old, and people older than 65 (52,58).…”
Section: Facet Joint Injurymentioning
confidence: 99%
“…For instance, in an animal study, it was shown that sequential removal of sheep capsular ligaments and cervical facets caused an undue increase in range of motion, especially in axial rotation, flexion and extension with caudal progression [ 31 ]. Human cadaver studies have also indicated that transection or injury of joint capsular ligaments significantly increases axial rotation and lateral flexion [ 32 , 33 ]. Specifically, the largest increase in axial rotation with damage to a unilateral facet joint was 294% [ 33 ].…”
Section: Cervical Capsular Ligamentsmentioning
confidence: 99%
“…Human cadaver studies have also indicated that transection or injury of joint capsular ligaments significantly increases axial rotation and lateral flexion [ 32 , 33 ]. Specifically, the largest increase in axial rotation with damage to a unilateral facet joint was 294% [ 33 ].…”
Section: Cervical Capsular Ligamentsmentioning
confidence: 99%